FORMATION OF CREATIVE ABILITIES STUDENTS IN STUDY PEDAGOGICAL DISCIPLINES AT THE FACULTY OF ARTS AND GRAPHICS - L. Savchenko (Academy of Cognitive and Natural Sciences, 2022)
In article opportunities of formation of creative abilities of Undents are shown during teaching pedagogical disciplines at art-graphic faculty.